Respecting Land Rights and Averting Land Disputes - UNCTAD (World Bank, Washington, DC, 2018)
This note provides guidance on how to ensure that agricultural investments respect existing land rights, both formal and informal, and thereby avert land disputes. Failure to respect land rights - in particular country - or region-specific land tenure systems and history, including use by pastoralists - has negative consequences for communities and other stakeholders. It is also financially damaging for investors who shortcut due process and end up spending time and money dealing with land disputes.